Traffic engineering standards in IP-networks using MPLS. - Ghanwani, A. (IEEE Communications magazine)
The explosive growth of the Internet over the last few years has made the IP protocol suite the most predominant networking technology. Furthermore, the convergence of voice and data communications over a single network infrastructure is expected to happen over IP-based networks. Traditional IP-networks offer little predictability of service, which is often unacceptable for applications such as telephony, as well as for emerging and future real-time applications such as telemedicine. One of the primary goals of traffic engineering is to enable networks to offer predictable performance. Due to the need for better traffic control by network service providers, there has been considerable activity in the Internet Engineering Task Force to develop standards for traffic engineering in IP-based networks. This article discusses the direction taken by the IETF and some of the recent standardization efforts for traffic engineering using multiprotocol label switching (MPLS). Our primary focus is on the signaling protocols developed for this purpose